Police reform in Bangladesh: readiness for safeguarding human rights in postcolonial democracies - Kabir, Ahmedul (The University of Edinburgh, 2024)
This thesis explores the ten-year-long externally driven Police Reform Programme (PRP) from 2005 - 2015 in Bangladesh. It is the first piece of academic research to attempt to engage critically with the aims, achievements and limitations of the Police Reform Programme to make sense of the prospects and challenges of future police reforms in Bangladesh. Based on interviews with former police elites, civil servants, judges, politicians, consultants and members of civil society, this thesis offers in-depth insights into the Police Reform Programme. The Police Act of 1861 established colonial and authoritarian policing practices in Bangladesh. This Police Act of 1861 continues to govern the police, reflects a colonial mindset in coercive policing practices, and limits Bangladesh's political, social, economic, cultural and legal development trajectory. In this thesis, I show how the shortcomings of the Police Reform Programme have highlighted the need for the Bangladesh Police to take responsibility for establishing human rights-based democratic policing befitting a post-colonial and post-authoritarian society. I promote the role of the police force as a protector of human rights in a democracy. This human rights-based approach recalibrates the negotiation between the international donors, the recipient government and policing agencies in police reform of their respective strategic and vested interests. The Police Reform Programme has largely failed to inspire the police to engage in human rights-based democratic policing. One of the reasons for the failure was that the Police Reform Programme and the Bangladesh Police became victims of politics of convenience. The Police Reform Programme came under pressure created by Western countries' strategic interests in security, economy and foreign policy. The police committed themselves to the fight against terrorism and transnational crimes to safeguard Western strategic interests over human rights. In return, the police and the broader governance system gained legitimacy with the Western countries. The Police Reform Programme also became part of the commodifying police reform initiatives worldwide. Additionally, the police exacerbated their indulgence in the vested interests of politics, power and corruption, which had been inherent since the colonial days. Although external police reforms have the potential to stimulate democracy to some extent, the character of the democratic journey defines the path of police reform in Bangladesh. Western external drivers have been problematic because of their human rights implications on internal policing and internal democratic arrangements in Bangladesh. The inner Bangladesh experience – which continues to be challenging and shaped by colonial structures and contemporary Western-supported development – emerges in most empirical data. Overall, this thesis produces insights into how the human rights consciousness plays a crucial role in positioning internationally driven democratic police reform programmes in Bangladesh and other similar postcolonial and post-authoritarian political contexts in the future.
Keywords: Bangladeshi Police Reform Programme; human rights; Global South; democratic policing; Police Reform Programme; police governance; Bangladesh; police leadership; donor-driven police reforms; postcolonial